Environmental drivers of the leaf nitrogen and phosphorus stoichiometry characteristics of critically endangered Acer catalpifolium - Zhang, Yuyang; Cheng, Xiaoyu; Sha, Zhipeng; Lekammudiyanse, Manuja U.; Ma, Wenbao; Dayananda, Buddhi; Li, Shuang; Lyu, Ruiheng (Frontiers in Plant Science, 2022)
Acer catalpifolium is a perennial deciduous broad-leaved woody plant, listed in the second-class protection program in China mainly distributed on the northwest edge of Chengdu plain. However, extensive anthropogenic disturbances and pollutants emissions (such as SO2, NH3 and NOX) in this area have created a heterogeneous habitat for this species and its impacts have not been systematically studied. In this study, we investigated the leaf nitrogen (N) and phosphorus (P) content of A. catalpifolium in the natural distribution areas, and a series of simulation experiments (e.g., various water and light supply regimes, different acid and N deposition levels, reintroduction management) were conducted to analyze responses of N and P stoichiometric characteristics to environmental changes. The results showed that leaf nitrogen content (LNC) was 14.49 ~ 25.44 mg g-1, leaf phosphorus content (LPC) was 1.29~3.81 mg g-1 and the N/P ratio of the leaf (L-N/P) was 4.87~13.93. As per the simulation experiments, LNC of A. catalpifolium is found to be relatively high at strong light conditions (80% of full light), high N deposition (100 and 150 kg N ha-1), low acidity rainwater, reintroduction to understory area or N fertilizer applications. A high level of LPC was found when applied with 80% of full light and moderate N deposition (100 kg N ha-1). L-N/P was high under severe shade (8% of full light), severe N deposition (200 kg N ha-1), and reintroduction to gap and undergrowth habitat; however, low L-N/P was observed at low acidity rainwater or P fertilizer application. The nutrient supply facilitates corresponding elements uptake, shade tends to induce P limitation and soil acidification shows N limitation. Our results provide theoretical guidance for field management and nutrient supply regimes for future protection, population rejuvenation of this species and provide guidelines for conservation and nutrient management strategies for the endangered species.